Analisis Selisih Nilai Tukar dan Transaksi Mata Uang Asing Pada PT Indofarma Tbk dan Entitas Anak (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to find out how differences in exchange rates and foreign currency transactions apply to PT Indofarma Tbk and its subsidiaries. This research uses qualitative methods by collecting data sourced from the Company's website, journals and related articles. Based on this research, PT Indofarma Tbk and Subsidiaries have a difference between the exchange rate or exchange rate which occurs due to debt accruals, purchasing medical equipment and imported raw materials.